Adaptive NK cell responses in HIV/SIV infections: A roadmap to cell-based therapeutics?. Issue 6 (7th February 2019) - Ram, Daniel R; Manickam, Cordelia; Lucar, Olivier; Shah, Spandan V; Reeves, R Keith
Abstract: NK cells play a critical role in antiviral and antitumor responses. Although current NK cell immune therapies have focused primarily on cancer biology, many of these advances can be readily applied to target HIV/simian immunodeficiency virus (SIV)-infected cells. Promising developments include recent reports that CAR NK cells are capable of targeted responses while producing less off-target and toxic side effects than are associated with CAR T cell therapies. Further, CAR NK cells derived from inducible pluripotent stem cells or cell lines may allow for more rapid "off-the-shelf" access. Other work investigating the IL-15 superagonist ALT-803 (now N803) may also provide a recourse for enhancing NK cell responses in the context of the immunosuppressive and inflammatory environment of chronic HIV/SIV infections, leading to enhanced control of viremia. With a broader acceptance of research supporting adaptive functions in NK cells it is likely that novel immunotherapeutics and vaccine modalities will aim to generate virus-specific memory NK cells. In doing so, better targeted NK cell responses against virus-infected cells may usher in a new era of NK cell-tuned immune therapy. Graphical Abstract: Review on NK cell responses against virus-infected cells in a new era of NK cell-tuned innate immune therapy.